Putative occurrence of amentoflavone across Selaginella species inferred from HPLC Retention Time analysis - AHMAD DWI SETYAWAN; TATIK CHIKMAWATI; MIFTAHUDIN MIFTAHUDIN; PUSPA DEWI N. LOTULUNG; SUTARNO SUTARNO; SUGIYARTO SUGIYARTO; SUNARTO SUNARTO (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Setyawan AD, Chikmawati T, Miftahudin, Lotulung PDN, Sutarno, Sugiyarto, Sunarto. 2025. Putative occurrence of amentoflavone across Selaginella species inferred from HPLC Retention Time analysis. Biodiversitas 26: 6490-6501. Amentoflavone is a prominent biflavonoid frequently reported in the genus Selaginella and widely studied for its diverse biological activities. However, information on its distribution across species remains fragmented and largely restricted to isolated reports on individual taxa. This study aims to provide a comparative, compound-centric assessment of the putative occurrence of amentoflavone across multiple Selaginella species using a standardized Retention Time (RT)-based HPLC approach. Plant materials representing 20 samples from 17 Selaginella species were analyzed under uniform extraction and chromatographic conditions. An authentic amentoflavone reference standard was used to establish an external RT benchmark, and chromatograms recorded at 270 nm were qualitatively evaluated for RT correspondence within a predefined RT screening window centered on the reference peak. Occurrence was assessed using a presence–absence framework without quantitative estimation or multivariate analysis. Putative RT correspondence consistent with amentoflavone was detected in 9 of the 17 analyzed species, while several taxa consistently lacked detectable RT-matched peaks. The observed RT ranges among positive species were narrowly clustered, indicating stable chromatographic behavior of the detected signal across different plant matrices. Intraspecific comparisons revealed contrasting presence–absence outcomes among populations of the same species, highlighting population-level variability in detectable compound occurrence. The results demonstrate that putative amentoflavone occurrence in Selaginella is species-specific and not universally distributed across the genus. This study underscores the value of RT-based HPLC as an exploratory, hypothesis-generating screening tool for mapping compound occurrence across diverse taxa, while explicitly acknowledging its limitations in structural confirmation and sensitivity. By providing a qualitative baseline, this screening-based framework offers an initial biotechnological entry point for prioritizing Selaginella taxa for targeted metabolite validation and subsequent investigation using structure-confirming analytical techniques.